The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1590/0101-31571994-0799
|View full text |Cite
|
Sign up to set email alerts
|

O fisco e a inflação: uma interpretação do caso brasileiro

Abstract: Resumo As interpretações “fundamentalistas” disponíveis da inflação brasileira parecem incapazes de explicar por que o Brasil tem uma taxa de inflação tão alta com um déficit operacional do setor público tão pequeno. Procura-se explicar esse paradoxo com o uso dos conceitos de déficit potencial com inflação zero e erosão inflacionária das despesas orçamentárias do governo. Conclui-se que a resolução do conflito inflacionário brasileiro passa pela transferência, aos governos locais ou ao setor privado, de parce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
9
0
4
Order By: Relevance
“…When Google search for the term "Patinkin effect" is done, Cardoso (1998) is the first result, displaying the relevance of this work. In Brazil, the Patinkin effect is also known as the "Bacha effect" after the economist Edmar Bacha (1994) conducted empirical studies that suggested that the Patinkin effect dominated the Tanzi effect in periods of high Brazilian inflation (Giambiagi & Além, 2011, p.124). Cardoso (1998) mentions Bacha's paper and her work dialogues with his discussion.…”
Section: -Shifting Perspectives: Contesting Inertialism In Inflation ...mentioning
confidence: 99%
See 4 more Smart Citations
“…When Google search for the term "Patinkin effect" is done, Cardoso (1998) is the first result, displaying the relevance of this work. In Brazil, the Patinkin effect is also known as the "Bacha effect" after the economist Edmar Bacha (1994) conducted empirical studies that suggested that the Patinkin effect dominated the Tanzi effect in periods of high Brazilian inflation (Giambiagi & Além, 2011, p.124). Cardoso (1998) mentions Bacha's paper and her work dialogues with his discussion.…”
Section: -Shifting Perspectives: Contesting Inertialism In Inflation ...mentioning
confidence: 99%
“…When Bacha (1994) was elaborating the paper " O fisco e a inflação: uma interpretação do caso brasileiro" 149 , Brazilian inflation was at a four-digit mark hitting 1.000 per year. There was an unresolved paradox in the Brazilian finances: the coexistence of mega inflation and a relatively low budget deficit 150 .…”
Section: -Shifting Perspectives: Contesting Inertialism In Inflation ...mentioning
confidence: 99%
See 3 more Smart Citations